The risk profile of electronic nicotine delivery systems, compared to traditional cigarettes, on oral disease: a review - Zhang, Qing; Wen, Cai (Frontiers in Public Health, 2023)
The use of electronic nicotine delivery systems (ENDS) has exploded, especially among teenagers and new smokers, amid widespread awareness of the dangers of traditional tobacco and restrictions on smoking. However, the risk effects of ENDS on physical health, especially oral health, are still ambiguous. The purpose of this study was to review the available evidence on risks of ENDS on oral health, and compares the differences between ENDS and traditional cigarettes. For heavy smokers, transferring the addiction of tobacco to ENDS can be less harmful to periodontal condition and physical health but is not completely without risk. The components of ENDS vapor have cytotoxic, genotoxic, and carcinogenic properties, and its usage may be associated with a wide range of oral health sequelae. The chemicals in ENDS increase the susceptibility to tooth decay, increase the risk of periodontal disease, peri-implant, and oral mucosal lesions. Nicotine aerosols from ENDS can be a potential risk factor for oral cancer due to the presence of carcinogenic components. Compared to smoking traditional cigarettes, the harm associated with ENDS use may be underestimated due to the reduced ability to control vaping behavior, ease of ENDS access, fewer vaping area restrictions, and better taste. Currently, the available evidence suggests that ENDS may be a safer alternative to traditional tobacco products. Though most oral symptoms experienced by ENDS users are relatively mild and temporary compared to traditional cigarettes, the dangers of ENDS still exist. However, further research with longer follow-up periods is required to establish the long-term safety of ENDS.